Incidence of A.I. and TECD Assessment-Learning in University Students - Antonio , Manco Chávez José; Moisés , Galarza Espinoza Máximo; Alberto, Sosa Daniel; Enrique , Terrones Rojas Daniel; David , Licapa Tacuri; Héctor, Cerna Gonzales Carlos; Danny , Retamozo Riojas (Journal of Ecohumanism, 2024)
Currently it is seen a diversity in the use of digital tools emerging every day, so A.I. appears as an ally in the academic formation on the assessment-leaning and the TECD (Technology of digital knowledge empowerment). The main objective is to determine the incidence that exists between artificial intelligence and TECD assessment-leaning in the empowerment of digital knowledge in university students. The method used in the research is of basic type, with positivist paradigm of quantitative approach, because it measures the casual relationship that exists between the dependent variables, with non-experimental correlational causal design using surveys for data collection in the students at a university. In the results, it is obtained that 33.3% of students manage to empower themselves with digital knowledge creating materials within specific works according to their professional training lines; in the intermediate level, the result is that 35.9% of students manage to have a regular domain on programming systems and model new computer systems creating a computational system, neural network training and deep learning. In conclusion, data collection and analysis are powerful tools in the continuous improvement of education.